2018
DOI: 10.1002/ecs2.2305
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning the functional variation of tree seedlings during secondary succession in a tropical lowland rainforest

Abstract: The seedling stage is a key phase in the regeneration dynamics of forest communities. The functional diversity of tree seedlings is closely related to the structuring and functioning of forest ecosystems. Here, we examined and partitioned variations of tree seedlings in functional diversity over a chronosequence (younger secondary forest, 18–30 yr; older secondary forest, 60 yr; and old growth forest) after shifting cultivation in a tropical lowland rainforest area on Hainan Island, China. Results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The decline in the dominant species in the two different years changed; the species with greater decline ratios may be removed in the future for forest restoration. Moreover, it is reported that the species with lower decline ratios possibly conserve for longer periods of time [57]. Nonetheless, these species possibly create enough space for dominant species during their maturity.…”
Section: Plant Species Diversity and Dominant Species Role In Two Dif...mentioning
confidence: 99%
“…The decline in the dominant species in the two different years changed; the species with greater decline ratios may be removed in the future for forest restoration. Moreover, it is reported that the species with lower decline ratios possibly conserve for longer periods of time [57]. Nonetheless, these species possibly create enough space for dominant species during their maturity.…”
Section: Plant Species Diversity and Dominant Species Role In Two Dif...mentioning
confidence: 99%
“…The decline in the dominant species altered and species with higher decline ratios were possibly removed for forest conservation in the following years. Furthermore, species with lower decline ratios have been suggested to conserve for longer periods (Lu et al, 2018). However, at the secondary stage of succession, these species may be creating enough space for the most prevalent species.…”
Section: Variation In Community-weighted Mean Values Of Plant Functio...mentioning
confidence: 99%
“…Unraveling the sorption characteristics and mechanisms of PTEs on SBC from agricultural and forestry soils can help exploring the potential of BC or biochar in influencing the immobilization of PTEs in agricultural and forestry lands. The natural tropical rainforest in the Bawangling Forest Region (108.88°-109.33°E, 18.86°-19.20°N) of Hainan island in China (Lu et al, 2018) was rarely disturbed for replacing its plantations, and has therefore existed for several thousand years without any cultivation (Zhang et al, 2010;Wang et al, 2017a), except a serious damage caused by people for creating more farmland or for obtaining more forest resources about 600 years ago in the Ming Dynasty (Dodson et al, 2019). The lands nearby the Bawangling Forest Region have been cultivated for about years (Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The natural tropical rainforest in the Bawangling Forest Region (108.88°-109.33°E, 18.86°-19.20°N) of Hainan island in China (Lu et al, 2018) was rarely disturbed for replacing its plantations, and has therefore existed for several thousand years without any cultivation (Zhang et al, 2010;Wang et al, 2017a), except a serious damage caused by people for creating more farmland or for obtaining more forest resources about 600 years ago in the Ming Dynasty (Dodson et al, 2019). The lands nearby the Bawangling Forest Region have been cultivated for about years (Lu et al, 2018). Rubber trees near the Bawangling Forest Region was adopted as the secondary plantation under less intensive cultivation (cultivated about 20 years ago) system, while vegetables were grown twice a year in some lands under highly intensive cultivation system.…”
Section: Introductionmentioning
confidence: 99%